High Incidence Of Henoch Schonlein Purpura - Rai Reena; Mathew Anil; Srinivas C.R (Wolters Kluwer Medknow Publications, 2001)
Henoch schonlein purpura was suspected in 18 cases from July 1997 to July 1999. Histopathology and immunofluorescence confirmed the diagnosis. The incidence in India is not known. However, an incidence of 1.2 per million is reported from Suffolk UK. We report an incidence of 3 per million from July 1997 to 1998 and 7 per million from July 1998 to 1999.